Dukungan orang tua berhubungan dengan tingkat kemampuan perawatan diri anak tunagrahita - Sri Nur Hartiningsih; Eka Oktavianto; Pipin Nurhayati (Universitas Jenderal Achmad Yani Yogyakarta, 2021)
Background: a child with mental retardation is one of the children who is born with a mental intellectual disability so that he has difficulty doing academic tasks, establishing communication, and having social relations but can be trained to be independent. To be independent in terms of self care requires support from parents.Objective: to determine the relationship between parenteral support and the level of self care independence of mentally retarded children at the Pembina Special School of Yogyakarta. Methods: quantitave coreelation study with cross sectional approach. The population in this study were all parents, both fathers and mothers who had mentally retarded children at elementary school level in Negeri Pembina Special School of Yogyakarta, totaling 82 people. The sample in this study wa 82 respondents with the sampling technique using total sampling. The Hypothesis testing teachnique uses the kendall tau test. Results: The results showed that there were 57 respondents (69,5%) in adequate category of parental support, and 64 respondents (78,0%) who were independent in self-care for mentally retarded children. From the results of the Kendal tau test, the result obstained p value = 0,020 with a P value alpha = 0,05, then the P value <P alpha Value (0,020< 0,05) so that parental support has a relationship to the level of self-care independence of mentally retarded children. Conclusion: There is relationship between parental support and the level of self-care independence of mentally retarded children at the Pembina Special School of Yogyakarta.